How Does Profitability, Size, and Capital Affect Credit Risk?: Evidence from Islamic Banks in Asian Countries - Idah Zuhroh (Falah: Jurnal Ekonomi Syariah, 2022)
The study aims to analyze the effect of profitability, size, and capital on the credit risk of Islamic banks in Asian countries through the mediating variable of financing by path regression analysis. Data were obtained quarterly from 2015Q1 – 2020Q3. Method of the study usedcausal research design, namely research that has the main objective of proving a a relationship affecting and being influenced by the variables studied. The findings conclude that size and profitability significantly affect credit risk through the financing mediation variable.  Capital does not significantly reduce credit risk because it only functions to mediate financing. Meanwhile, increased financing will also increase the credit risk of Islamic banks in the Asian Region. The study can explain why there is an inconsistency of the effect profitability, size, capital, on credit risk because there is a financing mediation role. The implication of policy that the Islamic bankers in Asian countries must more prudent to manage financing so that credit risk is controlled.